Mies - Mertins, Detlef
Once criticized as “the destroyer of familiar traditions and the architect of cold technology and faceless bureaucracy,” the building art of Mies van der Rohe (1886–1969) is in fact “complicit and resistant, classical and modern, ordinary and extraordinary,” as the late scholar Mertins (1954–2011) observes in this searching, erudite monograph. Mertins (Modernity Unbound) illustrates—with majestic examinations of such designs as the Barcelona Pavilion, the Reichsbank project, 860–880 Lake Shore Drie, and the Seagram Building—how van der Rohe’s architecture resonates with tensions and binaries that embody but don’t resolve the problems of modernity. Most extraordinary is the way Mertins unpacks the complex cultural and philosophical contexts that van der Rohe was steeped in throughout his 60-year career: drawing extensively on the self-educated architect’s library, the author contextualizes the thought of Rudolf Schwarz, Romano Guardini, Max Scheler, and other thinkers whose works nourished the architect. The result is a fascinating survey of the architect’s intellectual concerns: questions of the body and soul, technology and nature, and the individual and the community. Complemented by over 700 photographs, sketches, and architectural plans, this text ranks highly in the Mies van der Rohe corpus.